Adapting Cognitive Remediation Group Therapy as an Online or Hybrid Intervention for People Aging With HIV and Cognitive Concerns: Focus Group Protocol. (3rd November 2022) - Eaton, Andrew D.; Hui, Jenny; Muchenje, Marvelous; Murzin, Kate; Chan Carusone, Soo; Ibáñez-Carrasco, Francisco; Novik, Nuelle; McCullagh, John W.; Nicolay, Susanne; Walmsley, Sharon L.
Cognitive impairment is a significant health issue for people aging with HIV/AIDS. Cognitive challenges can include forgetfulness, trouble concentrating, and increasing struggles to learn new skills, all of which contribute to poorer mental health and decreased quality of life. Although there is no specific drug therapy that can reverse the brain impairment, group therapies may help people aging with HIV and cognitive challenges to better cope with their symptoms when combined with their usual medical treatment and follow-up. This community-based study will involve peer-led focus groups to discuss cognitive remediation group therapy – a combination of mindfulness-based stress reduction and brain training activities tested in a pilot randomized, controlled trial – as an in-person intervention for people aging with HIV in 2019. Via a brief demographic survey and technology-mediated focus groups ( n = 40) in Ontario and Saskatchewan, we will determine how the intervention could be adapted in an online or hybrid format considering the ongoing COVID-19 pandemic. Content analysis will be employed whereby a team of independent coders will code the focus group transcripts in line with the co-design framework and "Double Diamond" model of developing interventions, including intervention structure, content, and mode of delivery. Given the aging of the HIV population in Canada, increasing support will be required in addition to medical care to improve quality of life, and proactively address concerns about cognition. This protocol provides a roadmap for adapting in-person psychosocial interventions using community-based and technology-mediated methods.